FIGURATIVE LANGUAGE ANALYSIS ON EFEK RUMAH KACA’S SONG LYRICS AT SINESTESIA 2015 ALBUM - Muhammad Iqbal; Husni Thamrin; Restu Dessy Maulida; Erik Rusmana (Universitas Pasundan, 2023)
Figurative language is one kind of the language styles to make the expression and the message of the speaker or writer is strengthened. Figurative language usually used in song lyrics. Sometimes, figurative languages existed in song lyrics can’t be understandable. One of the song lyrics that has a lot of figurative languages is songs from Sinestesia album by Efek Rumah Kaca. Therefore, this research is trying to analyze figurative languages existed in song lyrics on Efek Rumah Kaca’s album titled Sinestesia. The research is focused on analyzing type of figurative languages with its meaning by using Kennedy’s theory of classification of figurative language (1983) and Ogden and Richard’s theory of meaning (1923). Qualitative descriptive is the method that used for this research. The result of this research is 4 type of figurative languages is found, which is 25 personifications, 18 metaphors, 15 overstatements, and 2 apostrophes with each of figurative language’s meaning is elaborated. Besides of it, the writer found that figurative languages existed in the Sinestesia album’s song lyrics has a connection to the song itself.